Recent Advancements Surrounding the Role of the Periaqueductal Gray in Predators and Prey - Franklin, Tamara B. (Frontiers in Behavioral Neuroscience, 2019)
Recent advances in neural circuitry techniques, like optogenetics and chemogenetics, have allowed for a greater understanding of the periaqueductal grey (PAG) and its importance in predator and prey behaviours. These studies in rodents have highlighted the role of the rostrolateral PAG in hunting behaviours, and have demonstrated functional differences across the dorsal-ventral/rostral-caudal axes of the PAG associated with defensive behaviours. Human imaging studies have further demonstrated that the PAG is active during situations involving imminent threat suggesting that the function of the PAG is likely largely conserved across species. This mini-review highlights some of the recent advancements towards our understanding of the functional neuroanatomy of the PAG and its importance in the predator and prey behaviours that are critical for survival.